2019
DOI: 10.1213/ane.0000000000004344
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Hypoxemia by Induction Technique Among Infants and Neonates Undergoing Pyloromyotomy

Abstract: BACKGROUND: In patients presenting for pyloromyotomy, most practitioners prioritize rapid securement of the airway due to concern for aspiration. However, there is a lack of consensus and limited evidence on the choice between rapid sequence induction (RSI) and modified RSI (mRSI). METHODS: The medical records of all patients presenting for pyloromyotomy from May 2012 to December 2018 were reviewed. The risk of hypoxemia (peripheral oxygen saturation [S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Adjusted odds ratio (AOR) of hypoxemia for all patients having RSI vs mRSI was 2.8, and in subgroup analysis of neonatal patients, AOR was 6.5, indicating that younger, more vulnerable patients may derive even greater protective benefit from mRSI. Though pulmonary aspiration is a rare event, in the limited sample size of this study, there was again no indication that mRSI resulted in an observed increase in pulmonary aspiration . We have made routine use of modified RSI with low‐pressure positive pressure ventilation prior to intubation of infants with full stomach considerations part of our clinical practice.…”
Section: Oxygen Deliverymentioning
confidence: 80%
See 1 more Smart Citation
“…Adjusted odds ratio (AOR) of hypoxemia for all patients having RSI vs mRSI was 2.8, and in subgroup analysis of neonatal patients, AOR was 6.5, indicating that younger, more vulnerable patients may derive even greater protective benefit from mRSI. Though pulmonary aspiration is a rare event, in the limited sample size of this study, there was again no indication that mRSI resulted in an observed increase in pulmonary aspiration . We have made routine use of modified RSI with low‐pressure positive pressure ventilation prior to intubation of infants with full stomach considerations part of our clinical practice.…”
Section: Oxygen Deliverymentioning
confidence: 80%
“…The familiar structure of the blade and lack of angulation is expected to decrease technical complications compared with a hyperangulated blade . The ability to convert from a direct to indirect technique within the same airway attempt may minimize attempts, and thus, complications, as the need for multiple intubation attempts, have been associated with increased rates of hypoxemia even in otherwise healthy neonates and infants …”
Section: Pediatric Rigid Videolaryngoscopymentioning
confidence: 99%
“…In this issue of Anesthesia & Analgesia , Park et al 1 report results of an observational study on the risk of hypoxemia (defined as a peripheral oxygen saturation <90%) during rapid sequence induction (RSI) versus a modified RSI technique in infants and neonates undergoing pyloromyotomy. The authors used logistic regression to analyze the association between the induction technique and the risk of hypoxemia while controlling for potential confounders.…”
mentioning
confidence: 99%
“…Researchers can then study the relationship between each variable and the binary (dichotomous) outcome while holding constant the values of the other independent variables. This is particularly useful not only to understand the independent relationship of each variable with the outcome, but also, as done by Park et al, 1 to adjust the estimates for the effects of confounding variables 4 in observational research.…”
mentioning
confidence: 99%
See 1 more Smart Citation